NA ANALYSIS OF THE FUNCTIONS OF THE PERSONNEL AND HUMAN DEPARTMENT IN THE PREFECTURE OF NOVA MAMORÉ-RO (REMUNOM, 2025)
Currently, studies on public service functions, workplace appreciation, and the efficiency of people management in organizations are ongoing, aiming to improve relationships among all organizational stakeholders to deliver quality service. Therefore, based on the theme addressed, this study focuses on analyzing the functions performed in the Human Resources and Personnel Department that contribute to efficient and transparent service delivery and the appreciation of employees at the Nova Mamoré, Rondônia City Hall. The methodology used was based on a qualitative approach, which enabled a deeper understanding of the institutional reality from the perspective of the researcher and his interviewees, followed by an exploratory approach and bibliographic design. The results were analyzed based on the interviewees' statements, the researcher's experience, and document analysis. The conclusion reached was that the Human Resources department and the City Hall's Human Resources Department have been striving to adopt practices more aligned with human development and competency-based management. However, a lack of planning overloads operational tasks, as does the absence of ongoing training, employee appreciation, and the integration of new technologies. Thus, it is concluded that strengthening the Human Resources departments, differentiating them from the Personnel Department without completely separating them, through ongoing planning and training, as well as the integration of new technologies, is a viable and necessary path to ensuring employee appreciation, institutional development, and the provision of higher-quality and more efficient public services to society.